A Review Paper on Population Growth and Regulation (International Journal of Innovative Research in Engineering & Management, 2021)
The application of ecological concepts to  the examination of animal species and their surroundings  is the scientific discipline of wildlife ecology. A frequent  goal of research is to create practical techniques for  managing natural systems in order to achieve and maintain  balance among wildlife, ecosystems, as well as humans,  and this often results in baseline data that may be used to  guide wildlife management strategies. The term "wildlife"  isn't precisely defined, and it's been applied to anything  from vertebrates to all wild creatures and plants over time.  Wildlife management has generally centered on game  species, particularly traditionally targeted mammals and  birds, with both the goal of increasing their populations to  promote sport as well as subsistence hunting opportunities. In the 1960s, wildlife conservation as well as research  shifted to nongame animals and other taxa, such as reptiles,  amphibians, or even invertebrates. Critically endangered  species are a key problem in today's wildlife conservation,  and they are usually given priority over gaming species in  management plans. Many new quantitative techniques  have been developed in the last decade, and they are  becoming more important in wildlife management,  conservation, and research. The fundamental ideas and  concepts, as well as applications and contemporary trends  in animal ecology research, will be covered in this article.
Keywords: Animals; Mammals; Management; Population